New insights into carbon acquisition and exchanges within the coral–dinoflagellate symbiosis under NH 4 + and NO 3 − supply - Ezzat, Leïla; Maguer, Jean-François; Grover, Renaud; Ferrier-Pagès, Christine (Proceedings of the Royal Society. B, Biological sciences, 2015)
Anthropogenic nutrient enrichment affects the biogeochemical cycles and nutrient stoichiometry of coastal ecosystems and is often associated with coral reef decline. However, the mechanisms by which dissolved inorganic nutrients, and especially nitrogen forms (ammonium versus nitrate) can disturb the association between corals and their symbiotic algae are subject to controversial debate. Here, we investigated the coral response to varying N : P ratios, with nitrate or ammonium as a nitrogen source. We showed significant differences in the carbon acquisition by the symbionts and its allocation within the symbiosis according to nutrient abundance, type and stoichiometry. In particular, under low phosphate concentration (0.05 µM), a 3 µM nitrate enrichment induced a significant decrease in carbon fixation rate and low values of carbon translocation, compared with control conditions (N : P = 0.5 : 0.05), while these processes were significantly enhanced when nitrate was replaced by ammonium. A combined enrichment in ammonium and phosphorus (N : P = 3 : 1) induced a shift in nutrient allocation to the symbionts, at the detriment of the host. Altogether, these results shed light into the effect of nutrient enrichment on reef corals. More broadly, they improve our understanding of the consequences of nutrient loading on reef ecosystems, which is urgently required to refine risk management strategies.